2017
DOI: 10.1016/j.fgb.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The high-affinity phosphodiesterase PdeH regulates development and aflatoxin biosynthesis in Aspergillus flavus

Abstract: Cyclic AMP signaling controls a range of physiological processes in response to extracellular stimuli in organisms. Among the signaling cascades, cAMP, as a second messenger, is orchestrated by adenylate cyclase (biosynthesis) and cAMP phosphodiesterases (PDEs) (hydrolysis). In this study, we investigated the function of the high-affinity (PdeH) and low-affinity (PdeL) cAMP phosphodiesterase from the carcinogenic aflatoxin producing fungus Aspergillus flavus, and found that instead of PdeL, inactivation of Pde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 39 publications
6
49
0
Order By: Relevance
“…Similar study has been reported in F. graminearum, the knockout of PDE gene pde1 resulted in increased production of secondary metabolite deoxynivalenol [23]. The deletion of PDE gene pdeH from A. avus led to an increased production of a atoxin to 110 mg/mL from 48 mg/mL [38].…”
Section: Improvement Of Monazps Yield In δ Mrpde Strainsupporting
confidence: 84%
“…Similar study has been reported in F. graminearum, the knockout of PDE gene pde1 resulted in increased production of secondary metabolite deoxynivalenol [23]. The deletion of PDE gene pdeH from A. avus led to an increased production of a atoxin to 110 mg/mL from 48 mg/mL [38].…”
Section: Improvement Of Monazps Yield In δ Mrpde Strainsupporting
confidence: 84%
“…The chloroform in sub-layer was dried in the fume hood overnight, and the precipitates were resuspended in 100 μl chloroform. TLC was used to analyse AF production, as described previously (Yang et al, 2017a). Briefly, 5 μl AF suspension was injected into a silica gel plate and separated by chromatographic solution including acetone: chloroform (1: 9, v/v).…”
Section: Afs Analysismentioning
confidence: 99%
“…About 100 μg of protein extracts derived from WT and mutants were then in-solution digested by trypsin (Promega) as previously described (Yang et al, 2017a). After trypsin digestion, an equal amount of the trypsindigested samples were diluted with 100 mM triethylammonium bicarbonate buffer and further processed according to the manufacturer's protocol for TMT 6plex isobaric label kit (Thermo Fisher Scientific).…”
Section: Protein Extraction Tmt Labelling and Lc-ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For the thin-layer chromatography (TLC) analysis and high-performance liquid chromatography (HPLC) analysis of aflatoxins (AF) production, WT, ∆Aflste20, and ∆Aflste20 C strains (10 7 spores/mL) were inoculated into 10 mL YES liquid media at 29 • C in dark for seven days, (30µL spore suspension per plate). After that, aflatoxin was extracted using a method previously described by Yang et al [44]. The supernatant samples were analyzed by TLC with a solvent system (chloroform: acetone = 9:1) and detected by ultraviolet light.…”
Section: Determination Of Afb1 Productionmentioning
confidence: 99%